Importance of viruses in acute otitis media - Nokso-Koivisto, Johanna; Marom, Tal; Chonmaitree, Tasnee (Current opinion in pediatrics, 2015)
Acute otitis media occurs as a complication of viral upper respiratory tract infection. Bacterial otopathogens and respiratory viruses interact and play important roles in acute otitis media development. A better understanding of viral and bacterial interactions may lead to innovative ways to lessen the burden of this common childhood disease. There has been increasing evidence that acute otitis media occurs during upper respiratory infection, even in the absence of nasopharyngeal bacterial colonization. Among the types of viruses associated with acute otitis media, respiratory syncytial virus continues to be the most commonly detected. It is still unclear whether viral load plays an important role in acute otitis media development, but symptomatic upper respiratory tract infection (as opposed to asymptomatic viral infection) is crucial. Widespread use of bacterial and viral vaccines in young children, including pneumococcal conjugate and influenza vaccines, has led to the reduction in otitis media-related healthcare use between 2001 and 2011. There has been no new vaccine against respiratory viruses other than influenza. Progress has been made toward the reduction of the burden of acute otitis media in the last decade. Success in reducing acute otitis media incidence will rely mainly on prevention of nasopharyngeal otopathogen colonization, as well as reduction in the incidence of viral upper respiratory tract infection.